Gamma spectrometric characterization of refractory products used in Turkey - Turhan, Şeref; Gündüz, Yunus; Varinlioğlu, Ahmet (Radiation Physics and Chemistry 97 (2014) 1–5, 2013)
This is the first detailed study related to the radiometric characterization of refractory materials produced for use in the industries of iron–steel, cement and glass manufacturing in Turkey. In this study, the activity concentrations of 226Ra, 232Th and 40K naturally occurring in 52 refractory material samples collected from Turkey's leading refractory factories were measured by using a gamma spectrometer with HPGe detector. Results show that the natural radioactivity of refractory material samples varies depending on raw material. The values of the activity concentrations of 226Ra, 232Th and 40K measured in the refractory brick and concrete samples varied from 1.3 to 384.2 Bq kg 1 (average: 173.5720.2 Bq kg 1), 2.9 to 392.9 Bq kg 1 (average: 176.7720.8 Bq kg 1) and 18.9 to 679.6 Bq kg 1 (average: 130.4723.9 Bq kg 1) and 24.0 to 158.2 Bq kg 1 (average: 73.3710.5 Bq kg 1), 25.0 to 134.4 Bq kg 1 (average: 76.3710.8 Bq kg 1) and 31.0 to 480.0 Bq kg 1 (average: 172.8740.5 Bq kg 1), respectively. The activity concentrations of 226Ra and 232Th measured in fireclay brick and high alumina brick samples are significantly higher than the average values of earth's crust.
Keywords: Refractory material, Natural radioactivity, Gamma-ray spectrometer